1978
DOI: 10.1080/15287397809529649
|View full text |Cite
|
Sign up to set email alerts
|

Influence of laying on lead accumulation in bone of mallard ducks

Abstract: Paired mallard ducks (Anas platyrhynchos) were given No. 4 lead shot, and bone lead concentrations were compared in drakes and in laying and nonlaying hens. Lead accumulation was significantly greater in bones with a high medullary content (femur and sternum) compared with bones with a lower medullary content (ulna-radius or wingbones). In dosed groups, hens always contained higher bone lead residues than drakes. After dosage with one shot (approximately 200 mg lead), lead in femurs of laying hens averaged 488… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Howdosing individuals with various amounts of lead shot (Jordan ever, many exist, On the and and Bellrose 195 ;Bellrose 1959;Longcore et al 1974; time of year. No data on the association of age and sex with ~i~~~~ et al 1976 ; Finley et 1976a; Dieter and Finley lead exposure in Canada geese (Branta canadensis) or other 1978; Finley and Dieter 1978;Trost 1981), assaying wing 'pecies Of geese are bones for lead concentrations (Anderson 1975;White and much is known about the of shot ingesstendell 1977; Stendell et al 1979), and examining gizzard tion and the occurrence of lead poisoning in waterfowl, little contents for ingested shot in hunter-killed ducks (Elder 1950; is about background lead levels Or how prevalence Of lead exposure varies among age and sex classes in a discrete during an annual cycle. We examined the preva- , and wintering grounds (Swan Lake National Wildlife Refuge (NWR)) of the Eastern Prairie Population of Canada geese.…”
Section: Introductionmentioning
confidence: 97%
“…Howdosing individuals with various amounts of lead shot (Jordan ever, many exist, On the and and Bellrose 195 ;Bellrose 1959;Longcore et al 1974; time of year. No data on the association of age and sex with ~i~~~~ et al 1976 ; Finley et 1976a; Dieter and Finley lead exposure in Canada geese (Branta canadensis) or other 1978; Finley and Dieter 1978;Trost 1981), assaying wing 'pecies Of geese are bones for lead concentrations (Anderson 1975;White and much is known about the of shot ingesstendell 1977; Stendell et al 1979), and examining gizzard tion and the occurrence of lead poisoning in waterfowl, little contents for ingested shot in hunter-killed ducks (Elder 1950; is about background lead levels Or how prevalence Of lead exposure varies among age and sex classes in a discrete during an annual cycle. We examined the preva- , and wintering grounds (Swan Lake National Wildlife Refuge (NWR)) of the Eastern Prairie Population of Canada geese.…”
Section: Introductionmentioning
confidence: 97%
“…In dosed birds, lead accumulated at high levels in feathers, reaching a level exceeding 900 n£ J. BURGER AND M. COCHFELD Longcore et al (1974) suggested that short-term high exposure and a long-term low-level exposure might have the same consequences with respect to the ultimate level of lead in the bone. Female mallards dosed by Finley and Dieter (1978) showed a dramatic increase in bone level with a single lead pellet dose compared with controls, but birds receiving two pellets had no higher levels than those exposed to one. Their accumulation curves match type C (female) and type B (males; Fig.…”
Section: Levels Of Lead In Herring Cull Chicks 227mentioning
confidence: 81%
“…White and Stendell (1977) found a high correlation between number of shot in gizzard and bone lead levels. Finley and Dieter (1978) point out that there are higher concentrations in bones with higher medullary content, femur and tibia have higher levels than the radio-ulna, and a low-calcium diet increases deposition of lead in bone. Pattee (1984) found no difference among the tibia and humérus of control kestrels, but a 2x increase in the tibias at a 10 ppm diet of lead, and a 4.7 x difference at 50 ppm.…”
Section: Levels Of Lead In Herring Cull Chicks 227mentioning
confidence: 97%
“…This would enhance the intestinal absorption of toxic metals. In ring doves (Streptopelia risoria; Kendall and Scanlon, 1981) and mallards (Anas platyrhynchos; Finley and Dieter, 1978), egg laying females revealed a greater uptake of lead in bone tissue than males (reviewed in Scheuhammer, 1987). This suggests differences between sexes in lead accumulation related to differences in calcium metabolism.…”
Section: Discussionmentioning
confidence: 98%